The impact of customer integration on manufacturing firms sustainable performance - Ghozali Hassan, Mohamad; Abindin, Rahimi; Nordin, Norani (International Journal of Engineering and Technology, 2018)
This paper examined the impact of customersâ€™ integration on the three dimensions of sustainability performance (environmental, economic and social) among manufacturing firms. The rationale for undertaking this study is based on the fact that many manufacturing firms, most especially within Malaysia have yet to adopt green supply chain management (GSCM) concept in their business operation, with GSCM recently emerging to ensure that firms comply with regulations for environmental protection. Even the few firms that have implemented this concept do not integrate their customers in the chain, which has led to the creation of an unhealthy culture. Although there are few prior studies that have investigated customers' integration on manufacturing firmsâ€™ sustainable performance, they have largely focused on sustainable performance only in terms of environmental dimension, excluding the economic and social dimensions. In this study, quantitative method was used for collecting data from 107 ISO14001 certified manufacturing companies in Malaysia. The statistical package for social science (SPSS) version 20.0 was used to analyze the data. The study findings indicate that customer integration has a positive and significant relationship with sustainable performance. Therefore, the study argues the need for customer integration to ensure a vibrant business organization performance.Â